EFFECT OF SUPPLEMENTAL CALCIUM ON REACTION AGAINST LEAF HOPPER AND MITE IN POTATO - Raj, B. T.; Kumar, Devendra; Minhas, J. S; Singh, B. P. (Potato Journal, 2013)
Use of supplementary Ca is one of the important criteria to mitigate the adverse effect of heat stress encountered invariably by early crop of potato. The interaction(s) between supplementary Ca and pest infestation, if any, has however not yet been worked out. Keeping this in view, experiments were conducted during early planting (2nd fortnight of September) in the years 2001 and 2002 at Modipuram to examine the reaction of heat tolerant genotypes/ variety, grown with and without Ca, against leaf hopper and mite. Potato cultivar Kufri Ashoka and heat tolerant genotypes namely HT/92-621 and HT/93-707 were grown with recommended fertilizers: @ 150 kg N, 80 kg P and 100 kg K per ha (control). In 2001, supplementary calcium was applied @ 50 kg and 100 Kg Ca/ ha in two equal doses using Ca(NO3)2. First half Ca-dose was applied at the time of planting and second half was applied at the time of earthing-up. In 2002, treatment of 50 kg Ca/ha was replaced by 4 foliar sprays of 100 ppm Ca at weekly intervals and a treatment of 200 kg Ca /ha was also added. Observations on the damage by leaf hoppers (Amrasca devastans) and mites (Polyphagotarsonemus latus) were recorded on 5 randomly selected plants from each plot at 45 and 60 DAP by visual scoring. Ca content of leaf was also analyzed. Supplementary calcium applied through soil increased the leaf Ca content in all the genotypes except in the treatment of 50 kg Ca/ha in cv. Kufri Ashoka. Genotype HT/92-621 maintained higher resistance to hopper burn with and without Ca application and the higher Ca content in leaves did not influence the resistance of the genotype against the pest and its reaction rating during both the years. Similar results were obtained in cv. Kufri Ashoka and HT/93-707 in respect to hopper burn. In case of mite damage the application of Ca did not alter the reaction ratings in genotype HT/92-621 in both the years. During 2002, the different application of Ca significantly increased the mite damage in cv. Kufri Ashoka and only in the treatment of 100 ppm foliar spray in genotype HT/93-707 as against the untreated control. Even though these enhancements in percent damage by mite were significantly higher, yet the reaction rating remained unchanged. These results demonstrated that, in general, Ca treatments did not alter the reaction ratings of different genotypes against leaf hopper and mite.